Dampak Revolusi Hijau dan Modernisasi Teknologi Pertanian: Studi Kasus Pada Budi Daya Pertanian Bawang Merah di Kabupaten Brebes - Haryono Rinardi; Noor Naelil Masruroh; Nazala Noor Maulany; Yety Rochwulaningsih (Jurnal Sejarah Citra Lekha, 2019)
Green Revolution is an effort to increase food production, especially in developing countries, by using agricultural modernization technology. This article identifies and evaluates some of the implementation impacts of technology modernization, in particular by taking a case study in the red onion cultivation in Brebes Regency. This study uses a historical method with a sociological approach that emphasizes the use of textual sources from newspapers and official reports, oral sources, and direct observation in the field. The results of this study found that through the Green Revolution, farmers were familiar with the use of artificial fertilizers, superior seeds, anti-pest pesticides, and so on. However, it led to high dependency on chemical fertilization, therefore production cost will be more inefficient. In the end, a large dependence of farmers also includes the fertilizer’s companies, namely large companies that produce artificial fertilizers, pesticides and so on. In extreme terms, there is a new form of neo-colonialism in the cultivation system in developing countries.